Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.134
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Organize a Bag of Words into Sentences with Neural Networks: An Empirical Study

Abstract: Sequential information, a.k.a., orders, is assumed to be essential for processing a sequence with recurrent neural network or convolutional neural network based encoders. However, is it possible to encode natural languages without orders? Given a bag of words from a disordered sentence, humans may still be able to understand what those words mean by reordering or reconstructing them. Inspired by such an intuition, in this paper, we perform a study to investigate how "order" information takes effects in natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this way, the CNN model encapsulates the feature extractor (HoG/SIFT) [14], the encoder (bag of visual words) [15], and the classifier (support vector machines [16]) all in itself. One of the first practical and widely adopted DL models was AlexNet (Pernik, Bulgaria), which played a pivotal role in showcasing the capabilities of CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the CNN model encapsulates the feature extractor (HoG/SIFT) [14], the encoder (bag of visual words) [15], and the classifier (support vector machines [16]) all in itself. One of the first practical and widely adopted DL models was AlexNet (Pernik, Bulgaria), which played a pivotal role in showcasing the capabilities of CNNs.…”
Section: Introductionmentioning
confidence: 99%
“…BERTbased LMs (Devlin et al, 2019) have demonstrated their abilities to encode various linguistic and hierarchical properties (Lin et al, 2019;Jawahar et al, 2019;Jo and Myaeng, 2020) which have a positive effect on the downstream performance (Liu et al, 2019a;Miaschi et al, 2020) and serve as an inspiration for syntax-oriented architecture improvements Bai et al, 2021;Ahmad et al, 2021;Sachan et al, 2021). Besides, a variety of pre-training objectives has been introduced (Liu et al, 2020a), with some of them modeling reconstruction of the perturbed word order (Lewis et al, 2020;Tao et al, 2021;Panda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%